Competitiveness and Factors Affecting Indonesia’s Natural Rubber Export: An Evidence from Eight Main Destination Countries - Novaldi, Jeremia; Muchlisoh, Siti (Faculty of Economic and Business, 2025)
Research Originality: This research contribution focused on Indonesia's natural rubber productivity and the role of importer industrial sector development in Indonesia's natural rubber exports.Research Objectives: This research analyzed Indonesia's natural rubber export competitiveness and the effect of productivity, importer industrial sector development, and export price on Indonesia's natural rubber export volume.Research Methods: This research used secondary data from the World Bank, FAO, and UN Comtrade. The dataset covers eight countries from 2002 to 2022. Revealed comparative advantage (RCA), export product dynamics (EPD), and x-model potential export products are applied to analyze export competitiveness. In contrast, panel regression is applied to analyze the determinants of export.Empirical Results: The results showed that Indonesia's natural rubber competitiveness has declined since 2018. Nevertheless, Indonesia's natural rubber is still competitive, and its expansion in the main-destination countries is considered potential. Natural rubber productivity, importer industrial sector development, and export price positively and significantly impact natural rubber export volume.Implications: Indonesia's natural rubber competitiveness has declined. Hence, improving natural rubber quality would be suggested. Moreover, the positive impact of productivity can be maximized by building supporting infrastructure and upgrading production technologies.JEL Classification: C33, F14, Q17How to Cite:Novaldi, J., & Muchlisoh, S. (2025). Competitiveness and Factors Affecting Indonesia’s Natural Rubber Export: An Evidence from Eight Main Destination Countries. Etikonomi, 24(1), 175 – 190. https://doi.org/10.15408/etk.v24i1.37841.